Development of inexpensive device for methanol detection in hand sanitizer gel using manganese-doped zinc sulfide quantum dots modified by N-methylpolypyrrole - KHENTHAPHAK, Sophanat; JULEANG, Pakorn; WONSAWAT, Wanida; CHAILAPAKUL, Orawon; PUNRAT, Eakkasit (Journal of Metals, Materials and Minerals, 2023)
A method for methanol detection by an inexpensive device using a nanomaterial modified by N-methylpolypyrrole (NMPPY) has been developed. Manganese-doped zinc sulfide quantum dots (Mn/ZnS-QDs) were synthesized and then characterized by a fluorescence spectrophotometer to study their spectroscopic properties. Mn/ZnS-QDs were modified with NMPPy and studied by digital-image colorimetry to optimize conditions for methanol detection. A 2 mL of 3000 mg∙L–1 Mn/ZnS-QDs modified with 300 μL of 1000 mg∙L-1 of NMPPy was chosen to be a detecting reagent for methanol determination. Under the optimum conditions, the linear range was found to be 2%v/v to 50%v/v of methanol with R-square of 0.9434 and the sensitivity of 3.569 ´ 10–3 (%v/v)-1, whilst the limit of detection (LOD) was 19.5%v/v. The selectivity of this method was also studied with several solvents; it was proven selective for methanol. Furthermore, a prototype device with simple and inexpensive has been created. The analytical performances were studied; the linearity of methanol detection was found in the range of 20%v/v to 80%v/v with R-square of 0.9918 and the sensitivity of 3.38 ´ 10-3 (%v/v)-1. Finally, the newly developed device was applied to analyze samples of hand sanitizer gel by digital-image colorimetry with acceptable results.